Case reportSpontaneous resolution of iatrogenic dissection of the left main coronary artery extending to the thoracic and abdominal aorta - Perek, Bartłomiej; Lesiak, Maciej; Jemielity, Marek (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2013)
Iatrogenic coronary artery dissection extending to the ascending aorta is a rare complication of percutaneous coronary interventions. Coronary stent implantation is usually sufficient to control the injury. In this report we describe an unusual case of spontaneous resolution of both left main coronary artery and aortic wall dissection. The patient was not operated on due to the location of the initial tear in the distal part of the left main coronary artery. Moreover, in computed tomography (CT) thrombus formation in the false lumen of the dissected aorta was seen. The in-hospital course was uneventful. The last follow-up CT showed complete resolution of dissection.